2009
DOI: 10.1128/jvi.01826-08
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Reorganization of the Cytoprotective Cellular Chaperone Hsp27 during Herpes Simplex Virus Type 1 Infection

Abstract: Chaperone-enriched domains are formed in the nuclei of cells lytically infected with herpes simplex virus type 1 (HSV-1). These domains, called VICE, for virus induced chaperone enriched, contain Hsc70, Hsp70, Hsp40, Hsp90, polyubiquitinated proteins, and components of the proteasome machinery. Accumulating evidence indicates that these sites may be utilized during infection to sequester misfolded, modified, or otherwise unwanted proteins away from viral replication compartments, sites of robust transcription,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…Hsp90α induction was observed at both low and high concentrations of bortezomib treatment of glioma and head and neck cancer cells. HSP90 has been previously shown to be important for localization of HSV polymerase to the nucleus (17), thus we hypothesized that bortezomib-induced HSP90 induction could be critical for the increased viral replication and cell killing following combination treatment. To test this hypothesis, we examined the impact of Geldanamycin, an HSP90 inhibitor, on combination treatment-induced tumor cell cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Hsp90α induction was observed at both low and high concentrations of bortezomib treatment of glioma and head and neck cancer cells. HSP90 has been previously shown to be important for localization of HSV polymerase to the nucleus (17), thus we hypothesized that bortezomib-induced HSP90 induction could be critical for the increased viral replication and cell killing following combination treatment. To test this hypothesis, we examined the impact of Geldanamycin, an HSP90 inhibitor, on combination treatment-induced tumor cell cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular antioxidant chaperone Hsp27 enhances replication of the herpesvirus, most likely due to the increased oxidative stress in cells caused by viral infection (Mathew et al, 2009(Mathew et al, , 2010. The oxidative stress, one of the hallmarks of neurodegenerative diseases like AD and PD, is connected to mitochondrial dysfunction (Mancuso et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Hsp27 foci are distinct from and adjacent to VICE domains. In cells depleted for Hsp27, we find that virus replication is significantly reduced signifying an important, yet undefined, role for this cellular chaperone [5]. Taken together, these studies indicate that essential protein turnover decisions are made at VICE domains and that these decisions enhance virus replication, however; the role of Hsp27 in this process is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies with microinjected substrates for the 20S proteasome reveal that VICE domains are active sites of proteolysis [3]. Our lab recently reported that the antioxidant chaperone Hsp27 also forms foci in virus-infected nuclei [5]. Hsp27 foci are distinct from and adjacent to VICE domains.…”
Section: Introductionmentioning
confidence: 99%